Penentuan Tenaga Kerja Optimal Pada Stasiun Pengemasan PT. PQRS Berdasarkan Perhitungan Waktu Standart Metode Work Sampling - Triannisa, Rizka; Dewi, Sinta (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT. PQRS is an agro-industrial company that plays a role in processing fresh tea leaves into various ready-to-consume tea products. Because there is no definite time standard for the production process, the corporation cannot accurately estimate the number of workers needed based on the workload at each work station, especially the packaging station. It is hoped that by combining the work sample approach with conventional time measurement methods, the author will assist businesses in identifying the ideal number of workers. The average time for packaging tea during 60 observations was 219.94 seconds, and the average working time was 480 minutes or 28,800 seconds or 8 hours a day, according to calculations that had been carried out. The number of workers in the tea packaging section is based on labor requirements calculated using a work sampling approach. According to the calculation of labor requirements using the work sampling method, the number of employees in the tea packaging section, which previously required 21 employees, has now become 18 employees at the PT.PQRS tea packaging station